School Bullying Di SD Negeri 04 Kebak Jumantono Karanganyar Tahun 2016/2017 (Studi Kasus) - Rahmat Ardian, Dicky; , Drs. Suwarno, SH., M. Pd (2017)
The purposes of this research are: 1) To know the teacher's awareness of school bullying at Elementary School 04 of Kebak, 2) To know the act of school bullying at Elementary School 04 of Kebak, 3) To know the efforts made by Elementary School 04 of Kebak in order to overcome the school bullying problem. The type of this research is descriptive qualitative by using a case study design. The research's informants are the teacher of the second grade, the teacher of the fifth grade, the student of second grade and the student of the fifth grade. The data collecting techniques had been used are interview, observation and also documentation. The data had been analyzed by using data reduction, data presentation, conclusion and data verification. The data examination technique is done by using research triangulation and technique triangulation. As the result, 1) The teacher will have knowledge about the act of school bullying; it is proved by seeing that the teacher is very concerned and does not underestimate about the case of school bullying that occurred. 2) The act of school bullying such as: a) Some components of school bullying such as: the bully, the people who bullied and also the informer. b) Some forms of school bullying are: physical bullying, verbal bullying and psychological bullying. Physical bullying includes hitting and pinch. Verbal bullying includes making fun and mocking. Psychological bullying includes threatening and ostracism. 3) Some efforts to overcome that had be done such as: a) Counsel with patience, b) Communicating with the students which involved with school bullying case intensively, c) Searching for issue, d) Growing the sense of mutual love among friends. The conclusion of this research showed that The Elementary School 04 of Kebak has overcome the act of school bullying by using treatments done by competent teacher.